Clinical outcomes of frozen-thawed blastocysts with twice noninvasive chromosome screenings - Qiao, Yu; Geng, Shuangshuang; Zhang, Bin; Meng, Fanyu; Yang, Weimin; Wang, Chenyi; Yao, Yaxin; Zhao, Dunmei; Lu, Sijia; Cai, Liyi; Deng, Kai (Frontiers in Endocrinology, 2025)
Research QuestionDoes the double freeze–thaw procedure affect embryo quality or clinical outcomes for patients?DesignA retrospective study was conducted on patients undergoing noninvasive chromosome screening (NICS) from March 2018 to April 2024. Patients were divided into two groups: (1) the double freeze-thaw group, whose cryopreserved blastocysts underwent a second NICS after thawing because the first NICS test failed, and (2) the single freeze-thaw group, whose blastocysts were successfully analysed in the first NICS. The clinical outcomes included the detection success rate of NICS via the analysis of thawing culture medium and the live birth rate.ResultsA total of 275 patients and 1, 443 embryos were included, with a NICS detection failure rate of 6.7% (96/1, 443). 87 were re-analysed after a second NICS using their thawed culture medium; 57.4% (50/87) of these re-tested embryos were classified as grade A or B. Fifty-two embryos were thawed and transferred in the double freeze-thaw group. Compared with the morphological grading before the first freezing, the ICM grade of two embryos decreased from A to B, and the TE grade of two embryos decreased from B to C before the second freezing. The results showed that there were still no significant differences in the clinical pregnancy rate (56.52% vs. 57.14%, adjusted p=0.785), early miscarriage rate (21.98% vs. 25.00%, adjusted p=0.528), ongoing pregnancy rate (44.10% vs. 42.86%, adjusted p=0.516), and live birth rate (42.86% vs. 42.86%, adjusted p=0.736) in single freeze–thaw group and double freeze–thaw group.ConclusionsComparable clinical outcomes were achieved by re-applying NICS using the thawing culture medium compared to the single freeze-thaw group.